Circular RNAs as Prognostic Biomarkers in Renal Cell Carcinoma: A Systematic Review and Meta-Analysis - Liao, Dan; Lin, Qiu; Xiao, Huan; Zhang, Fenglian; Han, Qin (Frontiers in Genetics, 2022)
Background: Recently, several studies have shown that circRNAs play critical roles in renal cell carcinoma (RCC) oncogenesis and development. However, whether the level of circRNA expression in RCC is correlated with prognosis remains unclear. Hence, we conducted a meta-analysis to explore the association between circRNA expression levels and the prognosis of RCC patients. Methods: We systematically searched Ovid, Embase, PubMed, and Web of Science from January 1950 to June 2021 for the literature published in English. According to the Preferred Reporting Items for Systematic Reviews and Meta-Analysis (PRISMA) guidelines, we conducted a meta-analysis of 21 selected studies to confirm the association between the circRNA expression level and prognosis of RCC. Results: This meta-analysis included 20 articles and 1,559 RCC patients. The results showed that the high expression of oncogenic circRNAs (OS: HR = 2.04, 95% CI: 1.63–2.56, p = 0.20; PFS: HR = 2.82, 95% CI: 0.82–9.72, p = 0.03) and low expression of tumor-suppressor circRNAs (OS: HR: 1.92, 95% CI: 1.61–2.30, p < 0.05; PFS: HR: 2.40, 95% CI: 1.76–3.28, p = 0.36) were closely related to poor survival outcomes. Conclusion: The meta-analysis verifies that circRNAs can be potential prognostic biomarkers of RCC.